2021
DOI: 10.1002/cbic.202100517
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of the Biosynthetic Gene Cluster for the Indolizidine Alkaloid Iminimycin in Streptomyces griseus

Abstract: Indolizidine alkaloids, which have versatile bioactivities, are produced by various organisms. Although the biosynthesis of some indolizidine alkaloids has been studied, the enzymatic machinery for their biosynthesis in Streptomyces remains elusive. Here, we report the identification and analysis of the biosynthetic gene cluster for iminimycin, an indolizidine alkaloid with a 6‐5‐3 tricyclic system containing an iminium cation from Streptomyces griseus. The gene cluster has 22 genes, including four genes encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Furthermore, comparisons of the amino acid sequences of the KS Q and ACP L domains revealed similarities in the amino acid residues involved in the GfsA KS Q domain–ACP L interactions, suggesting that KS Q domains have a similar recognition mode for ACP L domains to that observed in GfsA. Together with our previously reported functional analysis of KS Q domains, ,, the present study has revealed that the KS Q domain is indeed highly functionally similar to the modular type I PKS KS domain. Our findings are expected to help understand the complicated functions of the KS domain of modular type I PKS, which plays a vital role in polyketide biosynthesis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, comparisons of the amino acid sequences of the KS Q and ACP L domains revealed similarities in the amino acid residues involved in the GfsA KS Q domain–ACP L interactions, suggesting that KS Q domains have a similar recognition mode for ACP L domains to that observed in GfsA. Together with our previously reported functional analysis of KS Q domains, ,, the present study has revealed that the KS Q domain is indeed highly functionally similar to the modular type I PKS KS domain. Our findings are expected to help understand the complicated functions of the KS domain of modular type I PKS, which plays a vital role in polyketide biosynthesis.…”
Section: Discussionsupporting
confidence: 80%
“…Although several PKS modules have different domain organizations, only the structures of full-length modules consisting of KS−AT−KR−ACP have been determined. 24,25,28,29 As a dynamic property of a KS−AT−KR− ACP module, it is proposed that the dimeric KS−AT−KR− ACP module adopts an asymmetric conformation with the binding of a single ACP domain to the KS homodimer when the KS domain functions (Figure S20B). 25 An artificial state that is crosslinked with the separated ACP L domain may cause a symmetric conformation of the GfsA loading module.…”
Section: T H Imentioning
confidence: 99%
“…As of today, four microbial species capable of producing indolizidines have been identified [12][13][14][15]. all four known bacterial producers of indolizidines belong to the family of actinomycetes, a diverse group of bacteria renowned for their ability to produce medically relevant natural products [16].…”
Section: Bioactive Metabolites From Microorganismsmentioning
confidence: 99%
“…Various cyclizidines exhibit low to moderate cytotoxicity [12,14]. Sreptomyces griseus OS-3601 produces iminimycins, another type of indolizidine derivatives (Figure 9), which carry a rare imine-cation [15]. Additionally, one indolizidine compound was created…”
Section: Known Actinomycetical Indolizidine-producersmentioning
confidence: 99%
See 1 more Smart Citation